Starfish eaudiobook - Fipps, Lisa (Listening Library, 2021)
A PRINTZ HONOR BOOK • Ellie is tired of being fat-shamed and does something about it in this poignant novel-in-verse. “In her debut novel, Starfish, Lisa Fipps confronts diet culture and fat phobia head-on. . . .  The book reads as if Ellie herself is writing these poems, which are accessible and engaging.”— The New York Times Book Review Ever since Ellie wore a whale swimsuit and made a big splash at her fifth birthday party, she's been bullied about her weight. To cope, she tries to live by the Fat Girl Rules—like "no making waves," "avoid eating in public," and "don't move so fast that your body jiggles." And she's found her safe space—her swimming pool—where she feels weightless in a fat-obsessed world. In the water, she can stretch herself out like a starfish and take up all the room she wants. It's also where she can get away from her pushy mom, who thinks criticizing Ellie's weight will motivate her to diet. Fortunately, Ellie has allies in her dad, her therapist, and her new neighbor, Catalina, who loves Ellie for who she is. With this support buoying her, Ellie might finally be able to cast aside the Fat Girl Rules and starfish in real life—by unapologetically being her own fabulous self.